Anti-inflammatory and anti-neuropathic effects of a novel quinic acid derivative from Acanthus syriacus - Karim Raafat (Mashhad University of Medical Sciences, 2019)
Objective: Acanthus syriacus (AS) is one of the valuable herbal plants with immunomodulatory potentials. The aim of this study is to assemble a phytochemical investigation of A. syriacus exploring its anti-inflammatory and antinociceptive properties, identification of its most active compound(s) and elucidating their structure and determining their mechanisms of action. Materials and Methods: Bio-guided fractionation and isolation-schemes were used utilizing RP-HPLC, CC, 1H- and 13C-NMR, and biological-models were used to evaluate their effects against inflammation and neuropathic-pain (NP). Results: The outcomes showed that the most active fraction (FKCA) of AS was identified. Two of the three components of FKCA were identified by chromatographic-methods, while the third compound was isolated, its structure was elucidated and its was named Kromeic acid (KRA); FKCA contained Ferulic acid (27.5%), kromeic acid (48.1%), and chlorogenic acid (24.4%). AS, FKCA and KRA showed significant (p˂0.05) anti-inflammatory and antinociceptive potentials in the management of allodynia and thermal-hyperalgesia in NP. AS and FCKA showed comparatively equipotent antinociceptive-effects. FKCA showed higher antinociceptive effects than KRA suggesting additive-effects among FKCA components. The anti-inflammatory, insulin secretagogue, oxidative-stress reducing, and protective effects against NO-induced neuronal-toxicity might be amongst the possible mechanisms of tested compounds to alleviate NP. Conclusion: Here, we report the isolation and structure elucidation of a novel quinic-acid derivative, KRA. A. syriacus, FKCA, and KRA might be used as a novel complementary approach to ameliorate a variety of painful-syndromes.